Fluorinated co-solvent electrolytes for high-voltage Ni-rich LiNi0.8Co0.1Mn0.1O2 (NCM811) positive electrodes - Chen, Mingming; Liu, Zezhao; Zhao, Xinzhe; Li, Kuihao; Wang, Kehuang; Liu, Zhishan; Xia, Lan; Yuan, Jinliang; Zhao, Ruirui (Frontiers in Energy Research, 2022)
Nickel-rich LiNi0.8Co0.1Mn0.1O2 (NCM811) is one of the most promising positive electrodes for utilization in the next-generation of lithium-ion batteries. Charging the NCM cells above 4.3 V is proposed to be beneficial for its reversible capacity. However, the high reactivity of the NCM811 usually results in parasitic electrolyte degradation, which is accelerated with the increase of the Ni content in the NCM positive electrodes, leading to the thickening of the positive electrode-electrolyte interphase during cycling. Herein, to counter this issue, we select partially fluorinated solvents, such as methyl 3,3,3-trifluoropropanoate (MTFP) and 1,1,1,2,2,3,3,4,4-nonafluoro-4-methoxybutane (NFMB), as a co-solvent for fluoroethylene carbonate (FEC)-based electrolytes, and detailed investigate theirs physical, chemical, and electrochemical properties for applications in NCM811 materials. Compared to the carbonate-based electrolyte without a fluorinated solvent, the electrolytes with a fluorinated co-solvent display an obviously enhanced cycling performance of the Li/NCM811 cells charged to above 4.5 V. This work suggests that fluorinated co-solvent electrolytes provide an alternative way to the high-concentration electrolyte for the design of new electrolyte systems for high energy density lithium-ion batteries.